Development and characterization of bacterial nanocellulose loaded with Boswellia serrata extract containing nanoemulsions as natural dressing for skin diseases - Karl, Berit; Alkhatib, Yaser; Beekmann, Uwe; Bellmann, Tom; Blume, Gabriele; Steiniger, Frank; Thamm, Jana; Werz, Oliver; Kralisch, Dana; Fischer, Dagmar (International Journal of Pharmaceutics, 2020)
The combination of the anti-inflammatory lipophilic Boswellia serrata extract with the natural hydropolymer bacterial nanocellulose (BNC) for the treatment of skin diseases is counteracted by their different hydro/lipophilicity. To overcome the hydrophilicity of the BNC, the water in its network was exchanged by single and double nanoemulsions. Incorporation of the Boswellia serrata extract in the nanoemulsions formed particles of about 115 to 150 nm with negative zeta potential and storage stability over 30 days at temperatures between 4 and 32 °C. Their loading into the BNC did not change the preferential characteristics of the nanocellulose like water absorption and retention, softness, and pressure stability in a relevant way. Loaded BNC could be sterilized by an electron-beam procedure. A biphasic drug release profile of lead compounds was observed by Franz cell diffusion test. The biocompatibility of the loaded BNC was confirmed ex ovo by a shell-less hen's egg test. Tape stripping experiments using porcine skin determined a dependency of the drug penetration into skin on the type of nanoemulsion, single vs. repeated applications and the incubation time. In conclusion, the hydrophilicity of BNC could be overcome using nanoemulsions which offers the possibility for the anti-inflammatory skin treatment with Boswellia serrata extract.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial nanocellulose; Boswellia serrata; Drug delivery; Inflammation; Nanoemulsion; Skin